Analisis Usability pada SIAPEL-TEGAS dalam Pengurusan KTP-el dengan Menggunakan Metode System Usability Scale (SUS) - vita mei fudnia watiningsih; Mochammad Anshori; Ahsanun Naseh Khudori (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
SIAPEL-TEGAS (Integrated Population Administration Information System) is a digital service provided by the Department of Population and Civil Registration of Malang City that enables citizens to process population administration documents, including electronic identity cards (e-KTP), online. This study aims to analyze the usability level of the SIAPEL-TEGAS application in e-KTP processing services using the System Usability Scale (SUS) method. Data were collected through an online questionnaire distributed to 50 respondents who had previously used the service, employing a purposive sampling technique. The questionnaire consisted of 10 standard SUS statements measured using a 5-point Likert scale. The results showed that the SIAPEL-TEGAS application achieved an average SUS score of 85.35, which falls into the "Acceptable" category with a Grade A rating and an "Excellent" adjective rating. The validity test of all questionnaire items indicated that the calculated correlation coefficients (r-count) were higher than the critical value of r-table (0.2732), confirming that all items were valid. Meanwhile, the reliability test using Cronbach’s Alpha produced a value of 0.738, which is categorized as reliable (acceptable). These findings indicate that the SIAPEL-TEGAS application generally demonstrates an excellent level of usability in terms of effectiveness, efficiency, and user satisfaction. However, several aspects still require improvement to further optimize the user experience.